P4_2 How to fly your dragon - Fenlon-Smith, D; Jupp, M; Yeomans, K; Cobley, D (Physics Special Topics, 2016)
In this paper we calculate the minimum area and length of a dragon’s wing for it to be able to fly. The minimum area was calculated to be 224m^2 and the length was 35.6m.